Insulinoma and Chronic Kidney Disease: An Uncommon Conundrum Not to Be Overlooked. (18th November 2017) - Foppiani, Luca; Panarello, Serena; Filauro, Marco; Scirocco, Maria Concetta; Cappato, Stefano; Parodi, Andrea; Sola, Simona; Antonucci, Giancarlo
A hypertensive man with chronic kidney disease (CKD) secondary to polycystic disease was hospitalized for symptoms related to hypoglycemia. Fasting test elicited symptomatic hypoglycemia after 12 hours, which was associated with inappropriately unsuppressed normal insulin and C-peptide levels. Neither ultrasonography (US) nor magnetic resonance imaging detected any pancreatic tumor. Endoscopic ultrasonography (EUS) showed a small isoechogenic nodule suspect for neuroendocrine tumor in the pancreatic head. 68 Gallium-DOTA-Tyr 3 -octreotide positron emission tomography/computed tomography revealed intense uptake by a small region in the pancreatic head. Surgical exploration together with intraoperative US confirmed the nodule in the pancreatic head and evidenced another hypoechogenic one in the uncinate process. Both nodules were enucleated, but only the latter, which had not been previously detected by EUS, proved compatible with insulinoma on combined histology and immunohistochemistry. After nodule enucleation, hypoglycemia resolved and did not relapse. Insulinoma, as a major cause of unexplained hypoglycemia, requires careful hormonal and instrumental workup. In patients with CKD, the interpretation of biochemical criteria for the diagnosis of insulinoma can be challenging. Localization techniques may display pitfalls. Surgery is curative in most patients but long-term follow-up is required.